Chronic administration of sodium nitrite prevents hypertension and protects arterial endothelial function by reducing oxidative stress in angiotensin II-infused mice - Ling, Wei Chih; Mustafa, Mohd Rais; Vanhoutte, Paul Michel; Murugan, Dharmani Devi (Elsevier, 2018)
Aim: Endothelial dysfunction accompanied by an increase in oxidative stress is a key event leading to hypertension. As dietary nitrite has been reported to exert antihypertensive effect, the present study investigated whether chronic oral administration of sodium nitrite improves vascular function in conduit and resistance arteries of hypertensive animals with elevated oxidative stress. Methods: Sodium nitrite (50 mg/L) was given to angiotensin II-infused hypertensive C57BL/6J (eight to ten weeks old) mice for two weeks in the drinking water. Arterial systolic blood pressure was measured using the tail-cuff method. Vascular responsiveness of isolated aortae and renal arteries was studied in wire myographs. The level of nitrite in the plasma and the cyclic guanosine monophosphate (cGMP) content in the arterial wall were determined using commercially available kits. The production of reactive oxygen species (ROS) and the presence of proteins (nitrotyrosine, NOx-2 and NOx-4) involved in ROS generation were evaluated with dihydroethidium (DHE) fluorescence and by Western blotting, respectively. Results: Chronic administration of sodium nitrite for two weeks to mice with angiotensin II-induced hypertension decreased systolic arterial blood pressure, reversed endothelial dysfunction, increased plasma nitrite level as well as vascular cGMP content. In addition, sodium nitrite treatment also decreased the elevated nitrotyrosine and NOx-4 protein level in angiotensin II-infused hypertensive mice. Conclusions: The present study demonstrates that chronic treatment of hypertensive mice with sodium nitrite improves impaired endothelium function in conduit and resistance vessels in addition to its antihypertensive effect, partly through inhibition of ROS production.